Physiological role of the cyclic hydroxamic acids - Pethő, Menyhért (Acta Biologica Szegediensis, 2002)
Roots of young seedleings of barnyard grass, maize , rye and wheat secret hydroxamic acids. Their compexes with Fe/lll/-ions are available sources of iron. It is possible that the cyclic hydroxamic acids play a role in the alternative mechanism of iron uptake. The hydroxamic acids secreted by barnayard grass roots have an allelopathic role by inhibiting the roots growth of rice.